Conductive film and conductive device

JP7639451B2Active Publication Date: 2025-03-05TOYO INK MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021053144
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-03-05
Estimated Expiration
2041-03-26

AI Technical Summary

Benefits of technology

【0017】 本発明では、導電性炭素材料(A)とバインダー樹脂(B)から形成される導電膜であって、導電膜の配向度を選択的に制御することで、炭素材料間で優れた導電ネットワーク形成を可能にし、優れた導電性、耐久性を両立することできる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639451000001
    Figure 0007639451000001
Patent Text Reader

Abstract

To provide a conductive film having excellent conductivity and durability.SOLUTION: A conductive film contains a conductive carbon material (A) and a binder resin (B). In the conductive film, the degree of orientation of a carbon (002) plane may be 70% or more as measured by X-ray diffraction (XRD); the 60° gloss may be 4-30; or the density is 1.2-2.0 g / cc; or the conductive carbon material (A) may contain two or more carbon materials having different average particle sizes.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] SUMMARY OF THE DISCLOSURE Embodiments of the present invention relate to conductive films and conductive devices. [Background technology]

[0002] In recent years, electronics has developed remarkably, and conductive materials used in various electronic devices are also required to be smaller, lighter, less expensive, and have a longer life under various usage environments. For example, when manufacturing the wiring for electronic device substrates or wiring for connecting electronic devices, a conductive composition with good conductivity is required, but conductive compositions using metal fillers such as silver and copper are generally used, and major issues such as cost and durability have yet to be resolved. On the other hand, conductive compositions using conductive carbon materials that do not use metals have also been widely studied, but due to insufficient conductivity, their use has been limited to semi-conductive applications such as antistatic applications.

[0003] In addition, various conductive carbon materials with low volume resistivity, such as graphite and carbon nanotubes, have been investigated to date. The volume resistivity of these conductive carbon materials is about 10 -2 Although it exhibits high conductivity of less than Ω cm, it is difficult to mix and disperse it uniformly in resins and solvents. This can lead to poor contact between the carbon materials in coatings and molded products obtained from conductive compositions containing conductive carbon materials, resins, solvents, etc., making it difficult to fully demonstrate the conductivity of the material.

[0004] Patent Document 1 describes a method of kneading expanded graphite with a thermoplastic resin while heating it. By heating, the graphite particles and the thermoplastic resin are kneaded in a fluid state, so the graphite particles can be dispersed appropriately, but it is difficult to say that the graphite material is uniformly distributed in the molded product, and there is a problem that the electrical conductivity and durability are insufficient.

[0005] Patent Document 2 describes a method for providing a resin composition with high rigidity and small anisotropy of electrical conductivity by kneading graphite with an aspect ratio of 3 or less with a thermoplastic resin. Although the isotropy of the composition is improved by using graphite with a small aspect ratio, the graphite powder is dry-pulverized, which causes structural destruction due to micronization and poor contact between the graphite powder particles, resulting in a problem of reduced electrical conductivity.

[0006] Patent Document 3 describes a method of orienting graphite powder in a certain direction by performing an orientation treatment on a composition containing a resin and plate-like graphite having a specific aromatic vinyl copolymer. By introducing an orientation process such as pressure molding and application of a magnetic field or electric field, it is possible to improve the contact between graphite particles without impairing the inherent properties of graphite, but there are problems with the running costs associated with this operation and the decrease in conductivity during long-term storage of the molded product. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Unexamined Patent Publication No. 2-204317 [Patent Document 2] JP 2001-60413 A [Patent Document 3] JP 2013-119577 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0008] In view of the above problems, an object of the present invention is to provide a conductive film having excellent conductivity and durability. [Means for solving the problem]

[0009] The present invention has been made in consideration of the above problems and relates to the following [1] to [7].

[0010] That is, the present invention relates to a conductive film containing a conductive carbon material (A) and a binder resin (B), which has a degree of orientation in the carbon (002) plane of 70% or more as measured by X-ray diffraction (XRD).

[0011] The present invention also relates to the conductive film, wherein the 60° gloss is 4-30.

[0012] The present invention also relates to the conductive film, wherein the density is 1.2 to 2.0 g / cc.

[0013] The present invention also relates to the conductive film, wherein the conductive carbon material (A) contains two or more types of carbon materials having different average particle sizes.

[0014] The present invention also relates to the conductive film, wherein the conductive carbon material (A) contains a boron-containing carbon material.

[0015] The present invention also relates to the conductive film, wherein the boron content of the boron-containing carbon material is 0.005 to 15 mol %.

[0016] The present invention also relates to a conductive device including the conductive film. Effect of the Invention

[0017] In the present invention, a conductive film is formed from a conductive carbon material (A) and a binder resin (B), and by selectively controlling the degree of orientation of the conductive film, it is possible to form an excellent conductive network between the carbon materials, thereby achieving both excellent conductivity and durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described.

[0019] <Conductive carbon material (A)> In the present invention, the conductive carbon material (A) can be an inorganic carbon material. For example, carbon black (furnace black, acetylene black, ketjen black, medium thermal carbon black), graphite, fibrous carbon (carbon nanotube, carbon nanofiber, carbon fiber), carbon nanohorn, graphene, and fullerene can be used in combination of two or more. From the viewpoint of conductivity and availability, graphite, carbon black, fibrous carbon, and graphene are preferred, and it is more preferred to use two or more of carbon black, graphite, fibrous carbon, and graphene in combination.

[0020] Graphite is a hexagonal plate-like crystal of carbon, and for example, artificial graphite or natural graphite can be used. Artificial graphite is made by artificially orienting irregularly arranged micrographite crystals by heat treatment of amorphous carbon, and is generally produced using petroleum coke or coal-based pitch coke as the main raw material. Examples of natural graphite include amorphous graphite, lump graphite, and scaly graphite. In addition, examples of natural graphite include expanded graphite, flaked graphite with improved moldability and conductivity due to flaking, spheroidized graphite with reduced orientation due to spheroidization and crushing processing, and kish graphite, which is planarly crystallized carbon precipitated as the temperature of molten pig iron drops during hot metal pretreatment, etc. The expanded graphite is, for example, a powder obtained by immersing natural graphite or the like in a strongly oxidizing solution such as a mixture of concentrated sulfuric acid and nitric acid or a mixture of concentrated sulfuric acid and hydrogen peroxide to generate a graphite intercalation compound, rinsing with water, and then rapidly heating the compound to expand the C-axis direction of the graphite crystal, or a powder obtained by rolling the compound into a sheet and pulverizing the sheet. From the viewpoint of electrical conductivity in particular, it is preferable to use natural graphite.

[0021] Examples of commercially available graphite include flake graphite such as J-CPB, MCP-10, MCP-15, CPB, CB-150, FB-150, CB-100, FB-100, F#2, F#1, JB-5, ACP-1000, ACP, ACB-150, ACB-100, and ACB-50 manufactured by Nippon Graphite Industries Co., Ltd., and SRP7, SRP-150, SRP10, and 1500M-A manufactured by Ito Graphite Co., Ltd. Examples of flaky graphite include CMX, UP-5, UP-10, UP-20, UP-35N, CSSP, CSPE, CSP, CP, CB-150, CB-100, ACP, ACP-1000, ACB-50, ACB-100, and A manufactured by Nippon Graphite Industries. CB-150, SP-10, SP-20, J-SP, SP-270, HOP, GR-60, LEP, F#1, F#2, F#3, CX-3000 manufactured by Chuetsu Graphite Co., Ltd., FBF, BF, CBR, SSC-3000, SSC-600, SSC-3, SS Examples of the graphite include C, CX-600, CPF-8, CPF-3, CPB-6S, CPB, 96E, 96L, 96L-3, 90L-3, CPC, S-87, K-3, CF-80, CF-48, CF-32, CP-150, CP-100, CP, HF-80, HF-48, HF-32, SC-120, SC-80, SC-60, SC-32, EC1500, EC1000, EC500, EC300, EC100, EC50 manufactured by Ito Graphite Industries Co., Ltd., and 10099M and PB-99 manufactured by Nishimura Graphite Co., Ltd. Examples of the spherical graphite include CGC-20, CGC-50, CGB-6R, CGB-60R, and CGB-90R manufactured by Nippon Graphite Industries Co., Ltd. Examples of amorphous graphite include Blue P, AP, AOP, and P#1 manufactured by Nippon Graphite Industries Co., Ltd., and APR, S-3, AP-6, and 300F manufactured by Chuetsu Graphite Co., Ltd.Examples of artificial graphite include PAG-60, PAG-80, PAG-120, PAG-5, HAG-10W, and HAG-150 manufactured by Nippon Graphite Industries Co., Ltd.; RA-3000, RA-15, RA-44, GX-600, G-6S, G-3, G-150, G-100, G-48, G-30, and G-50 manufactured by Chuetsu Graphite Co., Ltd.; and SGP-100, SGP-50, SGP-25, SGP-15, SGP-5, SGP-1, SGO-100, SGO-50, SGO-25, SGO-15, SGO-5, SGO-1, SGX-100, SGX-50, SGX-25, SGX-15, SGX-5, and SGX-1 manufactured by SEC Carbon Co., Ltd., but are not limited to these, and two or more types may be combined.

[0022] The average particle size of the graphite is preferably from 0.5 to 500 μm, and particularly preferably from 2 to 200 μm.

[0023] The average particle size of the conductive carbon material (A) in the present invention can be calculated from the average value of carbon particles (aggregates; primary aggregates) randomly sampled in the conductive film using an optical microscope, an electron microscope, etc., and can also be calculated using image analysis, etc. The particle size in the conductive film is affected by, for example, the conductive carbon material (A) used and the dispersion state in the conductive composition for forming the conductive film.

[0024] Carbon black can be produced by continuously pyrolyzing a gaseous or liquid raw material in a reactor, particularly ketjen black made from ethylene heavy oil, channel black made by burning raw material gas and quenching and precipitating the flame by hitting the bottom surface of a channel steel, thermal black made from gas by periodically repeating combustion and pyrolysis, particularly acetylene black made from acetylene gas, etc. Carbon black that has been subjected to a commonly used oxidation treatment, hollow carbon, etc. can also be used.

[0025] Carbon oxidation is a process in which oxygen-containing polar functional groups such as phenol groups, quinone groups, carboxyl groups, and carbonyl groups are directly introduced (covalently bonded) to the carbon surface by treating the carbon at high temperatures in air or secondary treatment with nitric acid, nitrogen dioxide, ozone, etc., and is generally carried out to improve the dispersibility of carbon. However, since the electrical conductivity of carbon generally decreases as the amount of functional groups introduced increases, it is preferable to use carbon that has not been subjected to oxidation treatment.

[0026] The specific surface area of ​​the carbon black used is 20 m, calculated from the amount of nitrogen adsorbed (BET). 2 / g or more, 1500m 2 / g or less, preferably 50m 2 / g or more, 1500m 2 / g or less, more preferably 100m 2 / g or more, 1500m 2 It is preferable to use a material with a specific surface area of ​​20 m 2 When carbon black with a conductivity below 1500m / g is used, it may be difficult to obtain sufficient conductivity. 2 Carbon black exceeding this value may be difficult to obtain as a commercially available material.

[0027] The particle size of the carbon black used is preferably 0.005 to 1 μm, particularly preferably 0.01 to 0.2 μm, in terms of primary particle size.

[0028] Examples of commercially available carbon black include Tokai Carbon's Tokablack #4300, #4400, #4500, and #5500; Degussa's Printex L; Colombian's Raven7000, 5750, 5250, 5000ULTRAIII, 5000ULTRA, ConductexSCULTRA, Conductex975ULTRA, PUERBLACK100, 115, and 205; and Mitsubishi Chemical's #2350, #2400B, #2600B, #3050B, #3030B, #3230B, #3350B, #3400B, and #5 Examples of suitable blacks include furnace blacks such as MONARCH 400B, MONARCH 1400, 1300, 900, Vulcan XC-72R, and Black Pearls 2000 manufactured by Cabot Corporation, and Ensaco 250G, Ensaco 260G, Ensaco 350G, and Super P-Li manufactured by TIMCAL Corporation; ketjen blacks such as EC-300J and EC-600JD manufactured by Lion Corporation; and acetylene blacks such as Denka Black, Denka Black HS-100, and FX-35 manufactured by Denka Corporation, but are not limited to these. Two or more of these may be used in combination.

[0029] Conductive carbon fibers are preferably obtained by firing petroleum-derived raw materials, but those obtained by firing plant-derived raw materials can also be used. Carbon nanotubes are classified into single-walled carbon nanotubes, which form tubes with a diameter in the nanometer range with one graphene sheet, and multi-walled carbon nanotubes, which form tubes with multiple graphene sheets. Therefore, the diameter of multi-walled carbon nanotubes is large, at 30 nm, compared to the 0.7-2.0 nm of typical single-walled carbon nanotubes.

[0030] Examples of commercially available conductive carbon fibers and carbon nanotubes include vapor grown carbon fibers such as VGCF manufactured by Showa Denko K.K.; single-walled carbon nanotubes such as EC1.0, EC1.5, EC2.0, and EC1.5-P manufactured by Meijo Nano Carbon K.K.; FloTube9000, FloTube9100, FloTube9110, and FloTube9200 manufactured by CNano; NC7000 manufactured by Nanocyl Corporation; and 100T manufactured by Knano Corporation. Commercially available graphene-based carbons include, but are not limited to, graphene nanoplatelets xGnP-C-300, xGnP-C-500, xGnP-C-750, xGnP-M-5, xGnP-M-15, xGnP-M-25, xGnP-H-5, xGnP-H-15, and xGnP-H-25 manufactured by XG Sciences.

[0031] The conductive carbon material (A) preferably contains two or more kinds of carbon materials having different average particle sizes. The two or more kinds of carbon materials having different average particle sizes are not particularly limited, and different-sized particles made of the same kind of carbon materials may be used, or different-sized particles made of different kinds of carbon materials may be combined. By combining two or more kinds of carbon materials having different average particle sizes, for example, a conductive carbon material (A-1) with a conductive carbon material (A-2) having a smaller average particle size than the conductive carbon material (A-1), the packing property of the conductive film is improved, and the contact resistance between particles can be reduced, thereby enhancing the conductive network between the carbon materials.

[0032] <Boron-containing carbon materials> The conductive carbon material (A) is preferably a boron-containing carbon material doped with boron to replace at least a part of the carbon element in the carbon skeleton. The boron-containing carbon material is a carbon material having a basic skeleton of a hexagonal carbon mesh plane in which carbon atoms are covalently bonded in a hexagonal mesh pattern to form a mesh plane, and has physical and chemical interactions (bonds) between the structural units, and is doped with boron to replace at least a part of the carbon element. The boron-containing carbon material may contain hetero elements such as nitrogen and arsenic elements, and base metal elements, depending on the case.

[0033] As described later, the boron-containing carbon material is doped with boron to improve carrier density and / or mobility, so that the volume resistivity of the powder is smaller than that of a carbon material not doped with boron. In addition, compared to a carbon material not doped with boron, the surface state of the boron-containing carbon material changes, and for example, the wettability to resins and solvents tends to be higher. Therefore, the boron-containing carbon material can be dispersed well, and further, it is possible to simultaneously form an excellent conductive network and a resin coating having excellent strength.

[0034] From the viewpoint of electrical conductivity and durability, the conductive carbon material (A) is preferably a boron-containing carbon material. The boron-containing carbon material is preferably contained in the range of 0.1 to 100 mass% based on 100 mass of the conductive carbon material (A). The boron-containing carbon material is more preferably contained in the range of 20 to 100 mass%, and particularly preferably contained in the range of 50 to 100 mass%.

[0035] The content of boron element in the boron-containing carbon material (the content of boron in the entire carbon material) is not particularly limited, but is preferably 0.005 to 15 mol%, more preferably 0.01 to 2.5 mol%, and particularly preferably 0.01 to 1 mol%. If the content of boron is less than 0.005 mol%, it is difficult to obtain the doping effect of boron, and if the content of boron is 15 mol% or more, the excess boron may inhibit the movement of electrons, resulting in a decrease in conductivity. If the content is in the range of 0.005 to 15 mol%, good conductivity can be expressed. In addition, the inclusion of boron increases the affinity with organic solvents, dispersants, resins, etc., and improves the dispersibility of the dispersion liquid. On the other hand, a high boron content tends to increase the hardness of the carbon material, improving durability against external forces such as impact and coating strength. However, if the content exceeds 2.5 mol%, dispersion tends to become difficult. From the viewpoint of the strength and dispersibility of the carbon material, the boron content is preferably 2.5 mol% or less, and more preferably 1 mol% or less.

[0036] The content of boron in the boron-containing carbon material can be determined by a method such as ICP emission spectrometry or ICP mass spectrometry. An example is a measurement method in accordance with JIS-R7223. The form of boron in the boron-containing carbon material is not particularly limited. For example, substitutional boron element (BC3 type) in which a boron element is substituted at the position of a carbon element in a carbon skeleton, boron carbide type and boron cluster type boron element (B4C type, Bc type), boron oxide type boron element in a completely or partially oxidized state (BC2O type, BCO2 type, B2O3 type), etc. can be mentioned.

[0037] The boron-containing carbon material preferably has a ratio of boron element on the surface of the boron-containing carbon material of 0.01 to 10 mol%, more preferably 0.01 to 1 mol%, as measured by X-ray photoelectron spectroscopy (XPS). When the ratio of boron element is 0.01 to 10 mol%, a carbon material with excellent electrical conductivity can be obtained.

[0038] In addition, the ratio of substitutional boron element (BC3 type) on the surface of the boron-containing carbon material measured by X-ray photoelectron spectroscopy (XPS) is preferably 0.01 to 6 mol%, more preferably 0.01 to 1 mol%. Since the substitutional boron element (BC3 type) has the effect of improving carrier density, a carbon material with excellent electrical conductivity can be obtained. The ratio of substitutional boron element on the surface of the carbon material is expressed as B×BR, where B is the ratio of the spectral area of ​​all boron elements to the spectral area of ​​all elements on the carbon material surface measured by XPS, and BR is the ratio of the peak area of ​​substitutional boron elements to the spectral area of ​​all boron elements on the carbon material surface obtained from the B1s spectrum of XPS.

[0039] The B1s spectrum of boron obtained by XPS measurement appears in the binding energy range of the B1s electron of boron element (around 185 to 197 eV), and is known to be roughly divided into four components. The binding energy values ​​(peak tops) of each component are 186 to 187 eV for boron clusters, 187 to 188 eV for boron carbide, 188 to 189.3 eV for boron doped to replace carbon elements with a hexagonal mesh surface as the basic skeleton (BC3), 189.5 to 190.5 eV for various boron oxides BC2O, 191.5 to 192 eV for BCO2, and 192.5 to 193 eV for B2O3. When these peaks overlap, the ratio can be determined by fitting each component as a Gaussian function, optimizing the peak intensity, peak position, and full width at half maximum as parameters, and separating the peaks. Therefore, the state of boron on the surface of the boron-doped carbon material can be analyzed by performing peak separation of B1s.

[0040] The electrical conductivity of the boron-containing carbon material is expressed by the following formula. σ=μ×n×e (Formula 1) μ: mobility, n: carrier density, e: elementary charge (constant) According to the above formula (1), in order to improve the electrical conductivity, it is necessary to improve the mobility and / or carrier density. By doping a carbon material with boron, the carrier density and / or mobility is improved, and a carbon material with high electrical conductivity can be obtained.

[0041] Examples of boron-containing carbon materials include carbon black (furnace black, acetylene black, ketjen black, medium thermal carbon black), graphite, carbon nanotubes, carbon nanofibers, carbon nanohorns, graphene, graphene nanoplatelets, nanoporous carbon, carbon fibers, etc. These may be used alone or in combination of two or more kinds.

[0042] <Method for producing boron-containing carbon material> The method for producing the boron-containing carbon material of the present invention is not particularly limited, but is preferably a method including a step of mixing a carbon-based raw material (carbon source) with a compound containing boron (boron source) and a step of heat-treating the mixture at a high temperature of 1000° C. or more.

[0043] The raw material composition ratio of the carbonaceous raw material and the boron-containing compound for producing a boron-containing carbon material is not particularly limited, but the ratio of the boron-containing compound to 100 parts by mass of the carbonaceous raw material is preferably 0.01 to 300 parts by mass, and more preferably 0.1 to 100 parts by mass.

[0044] The method for preparing the mixture may include at least a carbonaceous raw material and a compound containing boron, and examples of the mixing method include dry mixing and wet mixing. As a mixing device, the following dry mixing device or wet mixing device can be used.

[0045] Examples of dry mixing devices include roll mills with two or three rolls, high-speed mixers such as Henschel mixers and super mixers, fluid energy grinders such as micronizers and jet mills, attritors, particle composite devices "Nanocure", "Nobilta", and "Mechanofusion" manufactured by Hosokawa Micron Corporation, and powder surface modification devices "Hybrid" manufactured by Nara Machinery Manufacturing Co., Ltd. Examples include the "Redization System", "Mechano Micros" and "Miraro".

[0046] In addition, when using a dry mixer, two or more raw materials may be directly mixed in powder form, but in order to prepare a more uniform mixture, one or more raw materials may be dissolved or dispersed in a small amount of solvent beforehand and then mixed. In order to further increase the processing efficiency, heating may be used.

[0047] Examples of wet mixing devices include mixers such as Disper, Homomixer, or Planetary Mixer, homogenizers such as M-Technique's "Clearmix" or PRIMIX's "Filmix", Red Devil's paint conditioner, ball mill, sand mills such as Shinmaru Enterprises' "Dynomill", attritor, or Coball Mill, media-type dispersers, wet jet mills such as Genus PY, Sugino Machine's "Starburst", Nanomizer's "Nanomizer", media-less dispersers such as M-Technique's "Clear SS-5" or Nara Machinery's "Micros", or other roll mills, kneaders, etc., but are not limited thereto. In addition, it may be preferable to use a wet mixing device that has been treated to prevent metal from entering the device.

[0048] For example, when using a media type disperser, it is preferable to use a method using a disperser whose agitator and vessel are made of ceramic or resin, or a disperser whose metallic agitator and vessel surface are treated with tungsten carbide spraying, resin coating, or the like. As the media, it is preferable to use ceramic beads such as glass beads, zirconia beads, or alumina beads. Also, when using a roll mill, it is preferable to use a ceramic roll. Only one type of dispersing device may be used, or multiple types of devices may be used in combination.

[0049] Furthermore, when the raw materials are not uniformly dissolved in the system, a general dispersant may be added together to disperse and mix the raw materials in order to improve the wettability and dispersibility of each raw material in the solvent.

[0050] The dispersant functions effectively as a dispersant for each raw material and can alleviate the aggregation. There are no particular limitations as long as it has the effect of alleviating aggregation, and any dispersant known in the art can be used. For example, dispersants such as resin-type dispersants, surfactants, and pigment derivatives can be used.

[0051] Examples of the resin-type dispersant include polyvinyl resins, polyurethanes, polyesters, polyethers, cellulose resins such as carboxymethyl cellulose, formalin condensates, silicones, and composite polymers thereof. Furthermore, these resin-type dispersants may be used in combination of two or more kinds. Polyvinylpyrrolidone, polyvinyl alcohol, polystyrene sulfonic acid, polyacrylic acid, carboxymethyl cellulose, etc. are preferred.

[0052] In the method of heat treating the mixture, the heating temperature is preferably 1000 to 3200°C, more preferably 1500 to 3000°C, although it varies depending on the types and amounts of the carbonaceous raw materials and the boron-containing compound used as raw materials.

[0053] The heating time is not particularly limited, but is usually preferably from 30 minutes to 10 hours.

[0054] Regarding the atmosphere in the heat treatment step, in order to prevent oxidation of the raw materials, an inert gas atmosphere such as nitrogen or argon, or a vacuum atmosphere is preferable.

[0055] In addition, the heat treatment process is carried out in one step under a certain atmosphere and temperature. It is also possible to carry out the reaction in multiple stages by changing the atmosphere or temperature each time.

[0056] <Carbon-based raw materials> Carbonaceous raw materials for producing boron-containing carbon materials are preferably inorganic carbonaceous raw materials. Specific examples of inorganic carbonaceous raw materials include graphite, carbon black (furnace black, acetylene black, ketjen black, medium thermal carbon black), activated carbon, carbon nanotubes, carbon nanofibers, carbon nanohorns, graphene, graphene nanoplatelets, nanoporous carbon, carbon fibers, and charcoal. Among the above carbonaceous raw materials, the size and lamination structure of the carbon hexagonal mesh surface vary depending on the type and manufacturer, and the crystallinity, particle size, shape, BET specific surface area, pore volume, pore size, bulk density, DBP oil absorption, surface acid-basicity, surface hydrophilicity, conductivity, and other physical properties and costs vary, so that the optimal material can be selected according to the application and required performance.

[0057] The carbon-based material is not particularly limited, but preferably contains at least one selected from graphite, carbon nanotubes, graphene nanoplatelets, and graphene.

[0058] <Boron-containing compounds> Next, a compound containing boron used in the production of a boron-containing carbon material will be described. The compound containing boron is not particularly limited, but examples thereof include boron carbide, boron oxide, boron nitride, metal borides, boron oxoacids, boranes, and boron-containing organic compounds. Specifically, in boron carbide, B4C(B 12 C3), B 12 C2(B6C) etc. Boron oxide includes BC2O, BCO2, B2O2, B2O3, B4O3, B4O5, etc. For boron nitride, BN, etc. Metal borides include AlB2, CoB, FeB, MgB2, NiB, TiB2, etc. Boron oxo acids include orthoboric acid, metaboric acid, tetraboric acid, etc. Boranes include monoborane, diborane, decaborane, etc. Examples of boron-containing organic compounds include borate esters such as trimethyl borate and triethyl borate, substituted boranes such as triethylborane and triphenylborane, and boronic acids such as phenylboronic acid and phenylboronic acid esters.

[0059] <Binder resin (B)>

[0060] The mass ratio of the binder resin (B) to the conductive carbon material (A) is not particularly limited, but is preferably 5:95 to 95:5, and more preferably 40:60 to 10:90.Within the above range, a conductive film having excellent adhesion can be obtained, and further, a conductive film having high conductivity and film strength can be obtained without the binder resin impeding contact between the carbon materials in the conductive film.

[0061] The binder resin may include one or more selected from the group consisting of polyurethane resins, polyamide resins, acrylonitrile resins, acrylic resins, butadiene resins, polyvinyl resins, polyvinyl butyral resins, polyolefin resins, polyester resins, polystyrene resins, EVA resins, polyvinylidene fluoride resins, polytetrafluoroethylene resins, silicone resins, polyether resins, cellulose resins such as carboxymethyl cellulose, etc. However, the binder resin is not limited to these resins. The binder resin may be used alone or in combination of two or more. From the viewpoints of volume resistivity, adhesion to the substrate, and durability, the binder resin preferably contains at least one selected from the group consisting of polyurethane-based, polyamide-based, and polyester-based resins, and more preferably polyurethane-based resins. In addition, the binder resin is preferably one that moderately softens or flows when the conductive composition is printed or coated on the substrate and then pressed or hot-pressed (hereinafter referred to as (hot) press). By using such a resin, the resin flows in the thickness direction while almost maintaining the planar pattern shape of the conductive film, the voids in the conductive film are reduced, and the contact points between the conductive carbon materials (A) are increased, so that a conductive film with low volume resistivity can be obtained.

[0062] <Polyurethane resin> The method for synthesizing the polyurethane resin is not particularly limited, but examples thereof include reacting a polyol compound (a) with a diisocyanate (b), reacting a polyol compound (a), a diisocyanate (b), and a diol compound (c) having a carboxyl group to obtain a urethane prepolymer (d) having an isocyanate group, further reacting the urethane prepolymer (d) with a polyamino compound (e), or, in the above three cases, reacting with a reaction terminator as necessary.

[0063] As the polyol compound (a), various polyether polyols, polyester polyols, polycarbonate polyols, polybutadiene glycols, or mixtures thereof, which are generally known as polyol components constituting polyurethane resins, can be used.

[0064] Examples of polyether polyols include polymers or copolymers of ethylene oxide, propylene oxide, tetrahydrofuran, and the like. Examples of polyester polyols include saturated and unsaturated low molecular weight diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, pentanediol, 3-methyl-1,5-pentanediol, hexanediol, octanediol, 1,4-butylenediol, diethylene glycol, triethylene glycol, dipropylene glycol, and dimer diol, as well as n-butyl glycidyl ether, 2-ethyl glycidyl ether, and the like. Examples of the polyester polyols include polyester polyols obtained by dehydration condensation of alkyl glycidyl ethers such as hexyl glycidyl ethers, monocarboxylic acid glycidyl esters such as versatic acid glycidyl ester, and dicarboxylic acids such as adipic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, succinic acid, oxalic acid, malonic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid, or anhydrides thereof, and polyester polyols obtained by ring-opening polymerization of cyclic ester compounds. Examples of polycarbonate polyols that can be used include 1) a reaction product of a diol or bisphenol with a carbonate ester, and 2) a reaction product of a diol or bisphenol with phosgene in the presence of an alkali. Examples of carbonate esters include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, and propylene carbonate. Examples of diols include ethylene glycol, propylene glycol, dipropylene glycol, diethylene glycol, triethylene glycol, butylene glycol, 3-methyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, and the like. Examples of bisphenols include bisphenol A, bisphenol F, and bisphenols obtained by adding alkylene oxides such as ethylene oxide and propylene oxide to bisphenols.

[0065] The number average molecular weight (Mn) of the polyol compound is appropriately determined taking into consideration the solubility of the polyurethane resin when producing the conductive composition, the durability of the conductive film formed, and the adhesive strength to the substrate, and is usually preferably in the range of 580 to 8,000, and more preferably 1,000 to 5,000. The polyol compounds may be used alone or in combination of two or more. Furthermore, a part of the polyol compounds may be replaced with low molecular weight diols, for example, various low molecular weight diols used in the production of the polyol compounds, within the range in which the performance of the polyurethane resin is not lost.

[0066] As the diisocyanate compound (b), an aromatic diisocyanate, an aliphatic diisocyanate, an alicyclic isocyanate, or a mixture thereof can be used, and isophorone diisocyanate is particularly preferred. Examples of aromatic diisocyanates include 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-benzyl isocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, tolylene diisocyanate, and xylylene diisocyanate.

[0067] Examples of the aliphatic diisocyanate include butane-1,4-diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and lysine diisocyanate. Examples of the alicyclic diisocyanate include cyclohexane-1,4-diisocyanate, isophorone diisocyanate, norbornane diisocyanate methyl, bis(4-isocyanate cyclohexyl)methane, 1,3-bis(isocyanate methyl)cyclohexane, and methylcyclohexane diisocyanate.

[0068] Examples of the diol compound (c) having a carboxyl group include dimethylolalkanoic acids such as dimethylolacetic acid, dimethylolpropionic acid, dimethylolbutanoic acid, and dimethylolpentanoic acid, dihydroxysuccinic acid, and dihydroxybenzoic acid. Dimethylolpropionic acid and dimethylolbutanoic acid are particularly preferred from the standpoint of reactivity and solubility. The conditions for reacting the polyol compound (a), the diisocyanate (b), and the diol compound (c) having a carboxyl group to obtain the urethane prepolymer (d) having an isocyanate group are not particularly limited except that the isocyanate group is in excess, but the equivalent ratio of the isocyanate group / hydroxyl group is preferably within the range of 1.05 / 1 to 3 / 1, and more preferably 1.2 / 1 to 2 / 1. The reaction is usually carried out at a temperature between room temperature and 150°C, and preferably between 60 and 120°C in terms of the production time and control of side reactions.

[0069] The polyamino compound (e) acts as a chain extender, and in addition to ethylenediamine, propylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, and norbornanediamine, amines having a hydroxyl group such as 2-(2-aminoethylamino)ethanol, 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, and di-2-hydroxypropylethylenediamine can be used. Among these, isophoronediamine is preferably used.

[0070] When the polyurethane resin is synthesized by reacting the urethane prepolymer (d) having an isocyanate group with the polyamino compound (e), a reaction terminator can be used in combination to adjust the molecular weight of the resulting polyurethane resin. As the reaction terminator, dialkylamines such as di-n-butylamine, dialkanolamines such as diethanolamine, and alcohols such as ethanol and isopropyl alcohol can be used.

[0071] The conditions for reacting the urethane prepolymer (d) having an isocyanate group with the polyamino compound (e) and, if necessary, with a reaction terminator are not particularly limited, but when the free isocyanate groups at both ends of the urethane prepolymer are taken as 1 equivalent, the total equivalent of the amino groups in the polyamino compound (e) and the reaction terminator is preferably within a range of 0.5 to 1.3, more preferably within a range of 0.8 to 0.995. The weight average molecular weight of the polyurethane resin is preferably in the range of 5,000 to 200,000 from the viewpoints of coatability and handleability.

[0072] <Polyamide resin> Polyamide resin is a general term for polymers having amide bonds obtained by various reactions such as polycondensation of dibasic acids and diamines, polycondensation of aminocarboxylic acids, or ring-opening polymerization of lactams. It includes various modified polyamides and those produced from partially hydrogenated reaction products. Polymers partially copolymerized with other monomers, or mixtures of other substances such as various additives can be used. The polyamide resin is not particularly limited, but a dimer acid modified polyamide resin obtained by condensation polymerization of a dibasic acid mainly composed of a dimer acid and a polyamine is preferable. As the dimer acid for producing the dimer acid modified polyamide resin, a dimer acid obtained by polymerizing a natural monobasic unsaturated fatty acid contained in tall oil fatty acid, soybean oil fatty acid, etc. is widely used industrially, but in principle, various dicarboxylic acids such as saturated aliphatic, unsaturated aliphatic, alicyclic, or aromatic may be used. Commercially available products of the dimer acid include Haridimer 200, 300 (manufactured by Harima Chemicals), Versadigm 228, 216, Empol 1018, 1019, 1061, 1062 (manufactured by Cognis), etc. Furthermore, hydrogenated dimer acid can also be used, and commercially available products of hydrogenated dimer acid include Pripol 1009 (manufactured by Croda Japan Co., Ltd.) and Empol 1008 (manufactured by Cognis). In addition to the above dimer acids, various dicarboxylic acids can be used as dibasic acids to obtain polyamide resins with suitable flexibility. Specific examples of dicarboxylic acids include oxalic acid, malonic acid, succinic acid (anhydride), maleic acid (anhydride), glutaric acid, adipic acid, vimelic acid, suberic acid, azelaic acid, sebacic acid, terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, 1,3- or 1,4-cyclohexanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, and 1,16-hexadecanedicarboxylic acid.

[0073] Furthermore, a dibasic acid having a phenolic hydroxyl group can also be used. By using a dibasic acid having a phenolic hydroxyl group, the phenolic hydroxyl group can be introduced into the side chain of the polyamide resin, and can be used in the reaction with the curing agent. Examples of dibasic acids having a phenolic hydroxyl group include hydroxyisophthalic acids such as 2-hydroxyisophthalic acid, 4-hydroxyisophthalic acid, and 5-hydroxyisophthalic acid; dihydroxyisophthalic acids such as 2,5-dihydroxyisophthalic acid, 2,4-dihydroxyisophthalic acid, and 4,6-dihydroxyisophthalic acid; dihydroxyterephthalic acids such as 2-hydroxyterephthalic acid, 2,3-dihydroxyterephthalic acid, and 2,6-dihydroxyterephthalic acid; hydroxyphthalic acids such as 4-hydroxyphthalic acid and 3-hydroxyphthalic acid; and dihydroxyphthalic acids such as 3,4-dihydroxyphthalic acid, 3,5-dihydroxyphthalic acid, 4,5-dihydroxyphthalic acid, and 3,6-dihydroxyphthalic acid. Further examples include acid anhydrides and ester derivatives such as polybasic acid methyl esters. Among these, 5-hydroxyisophthalic acid is preferred from the standpoints of copolymerizability, availability, and the like.

[0074] Furthermore, in order to obtain a polyamide resin with suitable fluidity when heated, various monocarboxylic acids are used as necessary, such as propionic acid, acetic acid, caprylic acid (octanoic acid), stearic acid, and oleic acid. The polyamines used as reactants in producing the dimer acid modified polyamide resin include, for example, various aliphatic, alicyclic and aromatic diamines, triamines and polyamines. Specific examples of the diamine include ethylenediamine, propanediamine, butanediamine, triethylenediamine, tetraethylenediamine, hexamethylenediamine, p- or m-xylenediamine, 4,4'-methylenebis(cyclohexylamine), 2,2-bis-(4-cyclohexylamine), polyglycoldiamine, isophoronediamine, 1,2-, 1,3- or 1,4-cyclohexanediamine, 1,4-bis-(2'-aminoethyl)benzene, N-ethylaminopiperazine, and piperazine. In addition, examples of triamines include diethylenetriamine, and examples of polyamines include triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, etc. Furthermore, dimer diamines obtained by converting a dimerized aliphatic nitrile group and reducing it with hydrogen can also be used.

[0075] Furthermore, examples of polyamine compounds include compounds in which the carboxyl group of a polybasic acid compound having a cyclic or acyclic hydrocarbon group having 20 to 48 carbon atoms is converted to an amino group. Examples of commercially available products include "Priamine 1071", "Priamine 1073", "Priamine 1074", and "Priamine 1075" manufactured by Croda Japan Co., Ltd., and "Versamine 551" manufactured by Cognis Japan Co., Ltd. The diamine may be used in combination with an alkanolamine. Examples of the alkanolamine include ethanolamine, propanolamine, diethanolamine, butanolamine, 2-amino-2-methyl-1-propanol, and 2-(2-aminoethoxy)ethanol. Also, polyether diamines having oxygen in the skeleton can be used. This polyether can be represented by the general formula H2N-R1-(RO)n-R2-NH2 (wherein n is 2 to 100, R1 and R2 are alkyl groups or alicyclic hydrocarbon groups having 1 to 14 carbon atoms, and R is an alkyl group or alicyclic hydrocarbon group having 1 to 10 carbon atoms. The alkyl group may be linear or branched). Examples of the ether diamine include polyoxypropylene diamine, and examples of commercially available products include Jeffamines (manufactured by Sun Techno Chemical Co., Ltd.). Also, bis-(3-aminopropyl)-polytetrahydrofuran can be used. The polyamines and dimer acids or various dicarboxylic acids are thermally condensed by a conventional method, and various polyamide resins including dimer acid modified polyamide resins are produced by an amidation process accompanied by dehydration. In general, the reaction temperature is about 100 to 300°C, and the reaction time is about 1 to 8 hours.

[0076] <Polyester resin> The polyester resin is a polymer composed of polyvalent carboxylic acid and polyhydric alcohol as monomers. Known polyester resins can be used, and specifically, from the viewpoint of ensuring the cohesive force of the resin, it is preferable that the weight average molecular weight is 1000 to 100000. From the viewpoint of adhesion, it is preferable that the glass transition temperature is -10°C to 200°C. Examples of the polyvalent carboxylic acid component include aromatic dicarboxylic acid, aliphatic dicarboxylic acid, unsaturated dicarboxylic acid, trivalent or higher carboxylic acid, etc., and one or more of these can be selected and used. On the other hand, examples of the polyhydric alcohol component include aliphatic glycol, ether glycol, trivalent or higher polyalcohol, etc., and one or more of these can be selected and used. Commercially available polyester resins include Vylon (manufactured by Toyobo Co., Ltd., "Vylon" is a registered trademark), Polyester (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., "Polyester" is a registered trademark), and Teslac (manufactured by Hitachi Chemical Polymer Co., Ltd., "Teslac" is a registered trademark).

[0077] From the viewpoints of fluidity during heating, volume resistivity, adhesion to the substrate, and durability, it is also preferable for the binder resin to contain a vinyl polymer having at least one structure selected from polyether, polyester, polycarbonate, and polybutadiene, which has a functional group capable of reacting with an isocyanate group, in the side chain. The method of introducing the side chain is not particularly limited, and it can be obtained by various synthesis methods.

[0078] Examples of functional groups capable of reacting with an isocyanate group include a hydroxyl group, an amino group, a carboxyl group, an epoxy group, an N-methylol group, and an N-alkoxymethyl group, with a hydroxyl group being preferred in terms of reactivity. The functional group capable of reacting with an isocyanate group can be introduced into the side chain or main chain of the vinyl polymer, and the method of introduction is not particularly limited and can be introduced by various synthesis methods. When used in applications requiring high toughness and durability, it is desirable to directly introduce a functional group capable of reacting with an isocyanate into the main chain of the vinyl polymer, which can improve the crosslink density of the resin.

[0079] The weight average molecular weight of the vinyl polymer in terms of polystyrene is preferably 5,000 to 500,000, and more preferably 10,000 to 100,000. When the weight average molecular weight of the polymer (A1) is 500,000 or less, the solubility in a solvent is improved, and when it is 5,000 or more, sufficient coating strength is obtained after (hot) pressing.

[0080] The binder resin may be a curable resin that undergoes a curing (crosslinking) reaction after the binder resin is applied to a substrate. The crosslinking agent used in the curable resin is not particularly limited, but may be a polyisocyanate compound having two or more isocyanate groups, etc. The polyisocyanate compound is not particularly limited, but when used outdoors, it is preferable to use only alicyclic or aliphatic compounds in order to prevent the coating film from deteriorating over time. Examples of the alicyclic polyisocyanate compound include isophorone diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated 4,4'-diphenylmethane diisocyanate. Examples of the aliphatic polyisocyanate compound include trimethylhexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate. Examples of aromatic polyisocyanate compounds include diphenylmethane diisocyanate, toluylene diisocyanate, naphthylene-1,5-diisocyanate, o-xylene diisocyanate, m-xylene diisocyanate, p-xylene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenylisocyanate. As the polyisocyanate compound, an adduct of the above compound with a glycol or a diamine, which has isocyanates at both ends, a biuret modified product, or an isocyanurate modified product may be used. In particular, when the polyisocyanate compound contains an isocyanurate modified product, particularly an isocyanurate ring-containing triisocyanate, sufficient coating strength can be obtained after heat pressing, which is preferable. Specific examples of the isocyanurate ring-containing triisocyanate include isocyanurate-modified isophorone diisocyanate (e.g., Desmodur Z4470 manufactured by Sumitomo Bayer Urethane Co., Ltd.), isocyanurate-modified hexamethylene diisocyanate (e.g., Sumidur N3300 manufactured by Sumitomo Bayer Urethane Co., Ltd.), and isocyanurate-modified toluylene diisocyanate (e.g., Sumidur FL-2, FL-3, FL-4, HLBA manufactured by Sumitomo Bayer Urethane Co., Ltd.). The polyisocyanate compounds may be used alone or in combination of two or more kinds, depending on the required performance, in such a ratio that the total number of isocyanate groups is preferably 0.1 to 5.0 times, more preferably 0.5 to 3.0 times, and particularly preferably 0.8 to 2.0 times, relative to the total number of functional groups of the binder resin.

[0081] The binder resin may be either a soluble resin that dissolves in a solvent described below, or a dispersion-type resin fine particle (emulsion) that does not dissolve in a solvent and exists in the form of fine particles. These may be used alone or in combination of two or more.

[0082] The particle structure of the dispersion type resin fine particles can be a multi-layer structure, so-called core-shell particles. For example, by localizing a resin obtained by mainly polymerizing a monomer having a functional group in the core or shell, or by providing a difference in Tg or composition between the core and the shell, it is possible to improve the curability, drying property, film-forming property, and mechanical strength of the binder. From the viewpoint of binding property and particle stability, the average particle diameter of the resin fine particles is preferably 10 to 1000 nm, and more preferably 10 to 300 nm. In addition, since the stability of the particles is impaired when a large amount of coarse particles exceeding 1 μm are contained, it is preferable that the amount of coarse particles exceeding 1 μm is at most 5% or less. In addition, the average particle diameter in the present invention represents the volume average particle diameter, and can be measured by a dynamic light scattering method. The measurement of the average particle diameter by a dynamic light scattering method can be performed as follows. Depending on the solid content of the resin fine particles, the resin fine particles are diluted 200 to 1000 times with the same dispersion liquid as the dispersion medium. About 5 ml of the diluted dispersion is poured into the cell of a measuring device (Nanotrack manufactured by Nikkiso Co., Ltd.), and the refractive index conditions of the dispersion medium and resin according to the sample are input, and then measurement is performed. The measurement can be performed based on the peak of the volume particle size distribution data (histogram) obtained at this time. The dispersed resin particles preferably contain crosslinked resin particles. The crosslinked resin particles refer to resin particles having an internal crosslinked structure (three-dimensional crosslinked structure), and it is important that the particles are crosslinked inside. In addition, the crosslinked resin particles contain specific functional groups, which can contribute to adhesion to the substrate. Furthermore, by adjusting the amount of the crosslinked structure and functional groups, a coating film with excellent durability can be obtained.

[0083] From the viewpoint of environmental load, etc., a water-soluble resin and aqueous resin fine particles that can be used in an aqueous solvent, preferably in water, are preferred. Also, from the viewpoint of slurry stability and coatability of the resin composition, it is more preferred to use a water-soluble resin and aqueous resin fine particles in combination.

[0084] <Water-soluble resin> A water-soluble resin is a resin that can be completely dissolved in water without separation or precipitation after 1 g of resin is added to 99 g of water at 25°C, stirred, and left to stand at 25°C for 24 hours. The water-soluble resin has the effect of increasing the dispersibility of the carbon material, so that a stable composition can be obtained with a small amount of resin. Water-soluble resins are broadly classified into anionic resins, cationic resins, amphoteric resins having both anionic and cationic properties, and nonionic resins other than those, and further, the resins may be composed of multiple monomers. Moreover, the water-soluble resins may be used alone or in combination of two or more kinds. Examples of anionic resins include resins containing a carboxyl group, a sulfo group, a phosphoric acid group, and a skeleton in which these groups are partially or completely neutralized. Examples of such resins include homopolymers of polymerizable monomers such as (meth)acrylic acid, itaconic acid, fumaric acid, maleic acid, 2-sulfoethyl methacrylate, and 2-methacryloyloxyethyl acid phosphate, copolymers with other polymerizable monomers, carboxymethyl cellulose, and alkali-neutralized products thereof. Cationic resins include those that contain cyclic amino groups and those that have been partially or completely neutralized. Examples of the polymerizable monomer include a resin containing a skeleton having a quaternary ammonium salt, etc. Examples of the polymerizable monomer include a homopolymer of a polymerizable monomer such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethyl (meth)acrylate, or vinylpyridine, or a copolymer with another polymerizable monomer, and an acid-neutralized product thereof. Examples of amphoteric resins include resins containing both the anionic skeleton and the cationic skeleton. An example of such a copolymer is styrene-maleic acid-N,N-dimethylaminoethyl (meth)acrylate. The nonionic resin is a resin other than the above-mentioned anionic, cationic and amphoteric resins. Examples of the polyvinylpyrrolidone include polyvinyl alcohol, polyvinyl butyral, polyacrylamide, poly-N-vinylacetamide, and polyalkylene glycol. The molecular weight of the water-soluble resin is not particularly limited, but the mass average molecular weight is preferably 5,000 to 2,500,000. The mass average molecular weight (Mw) refers to the molecular weight calculated as polyethylene oxide by gel permeation chromatography (GPC).

[0085] <Aqueous resin fine particles> Aqueous resin microparticles (aqueous emulsions) are dispersed resin microparticles in which the resin does not dissolve in water and exists in the form of fine particles, and examples of such microparticles include (meth)acrylic emulsions, nitrile emulsions, urethane emulsions, polyolefin emulsions, fluorine emulsions (polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE)), diene emulsions (styrene-butadiene rubber (SBR)), etc. Note that (meth)acrylic means either methacrylic or acrylic. When a coating film is formed from a resin composition containing aqueous resin microparticles, the resin composition has excellent adhesion between particles and to a substrate, and can provide a coating film with high strength. Furthermore, because of the excellent adhesion, only a small amount of aqueous resin microparticles is required, and as a result, the electrical conductivity of the resin composition is improved. In order to obtain the above-mentioned effects, the aqueous resin microparticles are preferably (meth)acrylic emulsions or urethane emulsions, which have excellent interparticle adhesion and flexibility (film flexibility).

[0086] The (meth)acrylic emulsion is an emulsion polymer containing 10 parts by mass or more of a monomer having a (meth)acryloyl group, preferably 20 parts by mass or more, more preferably 30 parts by mass or more. The monomer having an acryloyl group has excellent reactivity, so that resin microparticles can be relatively easily produced. Therefore, the (meth)acrylic emulsion is particularly preferable as the aqueous resin microparticle.

[0087] <Conductive composition> The conductive film of the present invention is preferably formed from a conductive composition containing a conductive carbon material (A), a binder resin (B), and, if necessary, a solvent.

[0088] <Solvent> When the carbon material and the binder are mixed uniformly, a solvent can be appropriately used. Such a solvent is not particularly limited as long as it can dissolve the resin or stably disperse the resin fine particle emulsion, and examples of the solvent include water and organic solvents.

[0089] The organic solvent may be appropriately selected as necessary from, for example, alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol methyl ether, and diethylene glycol methyl ether, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, ethers such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, and diethylene glycol dimethyl ether, hydrocarbons such as hexane, heptane, and octane, aromatics such as benzene, toluene, xylene, and cumene, esters such as ethyl acetate and butyl acetate, terpineol, dihydroterpineol, 2,4-diethyl-1,5-pentanediol, 1,3-butylene glycol, isobornylcyclohexanol, dimethyl sulfoxide, dimethylformamide, and N-methylpyrrolidone. The organic solvent is preferably a mixed solvent of toluene and propanol, dimethylformamide, or N-methylpyrrolidone, and more preferably a mixed solvent of toluene and propanol. The solvent may be water and an organic solvent, or two or more organic solvents may be used.

[0090] When using a water-soluble resin or aqueous resin particles, it is preferable to use water as a solvent from the viewpoint of solubility and dispersibility, and a liquid medium compatible with water may be added as necessary. As the liquid medium compatible with water, an alcohol-based solvent having a carbon number of 4 or less is preferable. In addition, various additives such as ultraviolet absorbers, ultraviolet stabilizers, radical scavengers, fillers, thixotropy-imparting agents, antiaging agents, antioxidants, antistatic agents, flame retardants, thermal conductivity improvers, plasticizers, anti-sagging agents, antifouling agents, preservatives, bactericides, defoamers, leveling agents, antiblocking agents, curing agents, thickeners, dispersants, and silane coupling agents may be added to the conductive composition as necessary, within the scope that does not impair the effects of the present invention.

[0091] <Dispersion machine / mixer> As an apparatus used in obtaining the conductive composition, a dispersing machine or a mixer that is generally used for dispersing pigments or the like can be used.

[0092] For example, mixers such as a Disper, Homomixer, or Planetary Mixer; homogenizers such as M-Technique's "Clearmix" or PRIMIX's "Filmix"; media-type dispersers such as a paint conditioner (Red Devil), ball mill, sand mill (Shinmaru Enterprises' "Dynomill", etc.), attritor, pearl mill (Eirich's "DCP Mill", etc.), or Coball mill; media-less dispersers such as wet jet mills (Zenus' "Zenus PY", Sugino Machine's "Starburst", Nanomizer's "Nanomizer", etc.), M-Technique's "Clear SS-5", or Nara Machine's "MICROS"; or other roll mills, but are not limited to these.

[0093] For example, when using a media type disperser, it is preferable to use a method using a disperser whose agitator and vessel are made of ceramic or resin, or a disperser whose metallic agitator and vessel surface are treated with tungsten carbide spraying or resin coating, etc. As the media, it is preferable to use glass beads, or ceramic beads such as zirconia beads or alumina beads. Only one type of dispersing device may be used, or multiple types of devices may be used in combination.

[0094] The conductive film of the present invention may be used alone or by being laminated on a substrate.

[0095] The method for applying the conductive composition to the substrate is not particularly limited, and any known method can be used.

[0096] Specific examples of the coating method include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting. Drying methods that can be used include, but are not limited to, standing to dry, blowing dryers, hot air dryers, infrared heaters, and far-infrared heaters.

[0097] The shape of the substrate is not particularly limited. Generally, a flat substrate is used. A flat film is used. However, substrates with a roughened surface, those treated with a primer, those with holes, and those with a mesh shape can also be used.

[0098] <Orientation of conductive film> The degree of orientation in the carbon (002) plane of the conductive film of the present invention, as measured by X-ray diffraction (XRD), is 70% or more, preferably 80%, more preferably 90%, and further preferably 92%. When the degree of orientation of the conductive film is 70% or more, the carbon particles having a graphite structure can be oriented in a certain direction, which promotes the movement of charge carriers of π-conjugated electrons consisting of sp2 hybrid orbitals, thereby achieving high conductivity. On the other hand, if the degree of orientation is less than 70%, the arrangement of the carbon particles in the composition becomes non-uniform, which inhibits the conductive network between the particles, thereby reducing the conductivity. The degree of orientation of the conductive film can be achieved to a desired value by adjusting the type and combination of carbon materials, the composition ratio, the dispersion method, etc. In addition, it can also be adjusted by using an external treatment such as a magnetic field, an electric field, or a press, if necessary.

[0099] <Conductive film gloss> The 60° gloss value of the conductive film of the present invention is preferably 4 to 30, more preferably 4 to 20, and even more preferably 4 to 15. There is a correlation between the 60° gloss value and the dispersion state of the conductive carbon material, and the higher the gloss value, the more uniformly and finely the conductive carbon material is dispersed. When the conductive film has a 60° gloss value of 4 to 30, the conductive carbon material is uniformly distributed and the conductive network is good. When the 60° gloss value is less than 4, the contact between the conductive carbon materials in the conductive layer becomes insufficient, and the conductivity of the conductive layer may be poor. In addition, when the 60° gloss value exceeds 30, the conductive carbon material is finely divided, which may cause partial destruction of the graphite structure, resulting in structural defects and a decrease in conductivity.

[0100] <Conductive film density> The density of the conductive film of the present invention is preferably 1.2 to 2.0 g / cc, and more preferably 1.4 to 1.8 g / cc. When the density of the conductive film is 1.2 to 2.0 g / cc, the contact between the conductive carbon materials in the conductive layer is good and the conductive network in the conductive layer is good, so that a conductive film having good adhesion to the substrate while maintaining excellent conductivity can be obtained.

[0101] <Conductive devices> The conductive film of the present invention has excellent conductivity and can be suitably used in devices that require conductivity. For example, it can be used as an electricity storage device such as a lithium ion battery or a capacitor, a power generation device such as a hydrogen fuel cell or a biopower generation device, a conductive wiring, an RFID, a semiconductor device such as a transistor or a sensor electrode. In particular, the conductive film of the present invention has excellent durability and can be suitably used in conductive wiring. EXAMPLES

[0102] The present invention will be described in more detail below with reference to examples, but the following examples are not intended to limit the scope of the invention. In the examples and comparative examples, "parts" refers to "parts by mass", and Mw refers to the weight average molecular weight.

[0103] <Production of boron-containing carbon materials> <Production Example 1> Scaly graphite F#2 (manufactured by Nippon Graphite Industries Co., Ltd.) and boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 90 / 10 (graphite / boric acid) and mixed in a mortar to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 2050°C for 1 hour to obtain a boron-containing carbon material (A-1-1).

[0104] <Production Example 2> Scaly graphite F#2 (manufactured by Nippon Graphite Industries Co., Ltd.) and boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 80 / 20 (graphite / boric acid) and mixed and composited using a particle compositer Mechanofusion (manufactured by Hosokawa Micron Corporation) to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 2050°C for 1 hour to obtain a boron-containing carbon material (A-1-2).

[0105] <Production Example 3> Scaly graphite F#2 (manufactured by Nippon Graphite Industries Co., Ltd.) and boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 95 / 5 (graphite / boric acid), and mixed and composited using a particle compositer Mechanofusion (manufactured by Hosokawa Micron Corporation) to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 2050°C for 1 hour to obtain a boron-containing carbon material (A-1-3).

[0106] <Production Example 4> Exfoliated graphite UP-20 (manufactured by Nippon Graphite Industries Co., Ltd.) and boric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 95 / 5 (graphite / boric acid), and mixed and composited using a particle compositer Mechanofusion (manufactured by Hosokawa Micron Corporation) to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 2050°C for 1 hour to obtain a boron-containing carbon material (A-2-1).

[0107] <Production Example 5> Ketjen Black EC300J (Lion Specialty Chemicals) and boric acid (Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a mass ratio of 95 / 5 (Ketjen Black / boric acid), and mixed and composited using a particle compositer Mechanofusion (Hosokawa Micron Corporation) to obtain a mixture. The mixture was filled into a graphite crucible and heat-treated in a multipurpose high-temperature furnace under an argon atmosphere at 2050°C for 1 hour to obtain a boron-containing carbon material (A-2-2).

[0108] The materials used in the examples and comparative examples are shown below. - F#2 scaly graphite (manufactured by Nippon Graphite Industries Co., Ltd.; hereafter abbreviated as "F#2") Exfoliated graphite UP-20 (manufactured by Nippon Graphite Industries Co., Ltd.; hereafter abbreviated as "UP-20") Spherical graphite CGB-50 (manufactured by Nippon Graphite Industries Co., Ltd., hereafter abbreviated as "CGB-50") - F#1 scaly graphite (manufactured by Nippon Graphite Industries Co., Ltd.; hereafter abbreviated as "F#1") Artificial graphite PAG-120 (manufactured by Nippon Graphite Industries Co., Ltd., hereafter abbreviated as "PAG-120") - Flaky graphite J-CPB (manufactured by Nippon Graphite Industries Co., Ltd., hereafter abbreviated as "J-CPB") Ketjenblack EC-300J (manufactured by Lion Specialty Chemicals, hereafter abbreviated as "EC300J") Denka Black HS-100 (manufactured by Denka Co., Ltd.; hereafter abbreviated as "HS100") Toka Black #5500 (manufactured by Tokai Carbon Co., Ltd.; hereafter abbreviated as "#5500") Graphene nanoplatelets xGnP-M-5 (manufactured by XGscience, hereinafter abbreviated as "GNP-M") (solvent) Toluene / isopropyl alcohol (mixture of 1 / 1 by weight) (hereinafter referred to as "toluene / IPA") - Ion-exchanged water (hereinafter referred to as "water")

[0109] The materials used in the examples and comparative examples were evaluated as follows. <Boron element content in conductive carbon material> The boron content in the carbon material was measured using an ICP emission spectrometer (SPECTROARCOS FHS12 manufactured by SPECTRO Inc.) The obtained value indicates the amount of boron contained in the entire carbon material.

[0110] <Average particle size of conductive carbon material> A part of the conductive film was cut out by Ar ion milling or Ga ion beam processing, and the carbon conductive film was photographed using a transmission electron microscope (JEM-1010, manufactured by JEOL Datum Co., Ltd.) at an accelerating voltage of 100 kV. The field of view and magnification were appropriately adjusted, and the diameter of the particles that formed the aggregate (primary agglomerate) was measured, and the measured values ​​of 100 particles were averaged to obtain the diameter.

[0111] <Synthesis of binder resin (B)> <Production Example 6> A reaction vessel equipped with a stirrer, thermometer, reflux condenser, dropping device, and nitrogen inlet tube was charged with 455.5 parts of a polyester polyol obtained from terephthalic acid, adipic acid, and 3-methyl-1,5-pentanediol ("Kuraray Polyol P-2011", Mn=2011, manufactured by Kuraray Co., Ltd.), 16.5 parts of dimethylolbutanoic acid, 105.2 parts of isophorone diisocyanate, and 140 parts of toluene, and the mixture was reacted at 90°C for 3 hours under a nitrogen atmosphere, and 360 parts of toluene was added to obtain a urethane prepolymer solution having isocyanate groups. Next, 969.5 parts of the obtained urethane prepolymer solution having isocyanate groups was added to a mixture of 19.9 parts of isophorone diamine, 0.63 parts of di-n-butylamine, 294.5 parts of 2-propanol, and 335.5 parts of toluene (the total equivalent of amino groups relative to the free isocyanate groups at both ends of the urethane prepolymer was 0.98), and the mixture was reacted at 50°C for 3 hours and then at 70°C for 2 hours. The mixture was diluted with 126 parts of toluene and 54 parts of 2-propanol to obtain a polyurethane resin solution with Mw=61,000 and acid value=10mgKOH / g.

[0112] <Production Example 7> In a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, inlet tube, and thermometer, 156.2g of Pripol 1009 as a polybasic acid compound, 5.5g of 5-hydroxyisophthalic acid, 146.4g of Priamine 1074 as a polyamine compound, and 100g of ion-exchanged water were charged and stirred until the temperature of the heat generation became constant. When the temperature stabilized, the temperature was raised to 110°C, and after confirming the outflow of water, the temperature was raised to 120°C after 30 minutes, and then the dehydration reaction was continued while raising the temperature by 10°C every 30 minutes. When the temperature reached 230°C, the reaction was continued at that temperature for 3 hours, and then the temperature was lowered by holding it under a vacuum of about 2kPa for 1 hour. Finally, an antioxidant was added to obtain a polyamide resin with a weight average molecular weight of 24,000, an acid value of 13.2KOHmg / g, a hydroxyl value of 5.5KOHmg / g, and a glass transition temperature of -32°C.

[0113] The resins were evaluated as follows. <Method of measuring weight average molecular weight (Mw)> The Mw was measured using a GPC (gel permeation chromatography) "HPC-8020" manufactured by Tosoh Corporation. GPC is a liquid chromatography that separates and quantifies substances dissolved in a solvent (THF; tetrahydrofuran) based on the difference in their molecular size. The measurement in the present invention was performed using two "LF-604" columns (manufactured by Showa Denko K.K.: GPC column for rapid analysis: 6 mm ID x 150 mm size) connected in series, at a flow rate of 0.6 ml / min and a column temperature of 40°C, and the weight average molecular weight (Mw) was determined in polystyrene equivalent.

[0114] <Acid value measurement> Approximately 1 g of sample was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture was added to dissolve it. Phenolphthalein test solution was added as an indicator and the solution was held for 30 seconds. After that, the solution was titrated with 0.1N alcoholic potassium hydroxide solution until it turned a pale pink color. The acid value was calculated using the following formula (unit: mgKOH / g). Acid value (mgKOH / g) = (5.611 x a x F) / S, where S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (ml) F: Potency of 0.1N alcoholic potassium hydroxide solution

[0115] <Adjustment of binder resin> The binder resins used in the examples and comparative examples were prepared into solutions with a solid content of 20% using the solvents shown below. · Urethane resin solution: The polyurethane resin obtained in Production Example (6) was diluted with toluene / isopropyl alcohol (mass ratio: 1 / 1) to obtain a polyurethane resin solution. Polyamide resin solution: The polyamide resin obtained in Production Example (7) was diluted with toluene / isopropyl alcohol (mass ratio: 2 / 1) to obtain a polyamide resin solution. Polyester resin solution: Vylon 200 (Toyobo Co., Ltd., polyester resin) was diluted with toluene / methyl ethyl ketone (mass ratio: 1 / 1) to obtain a polyester resin solution.

[0116] <Conductive film> Example 1 Among the conductive carbon materials (A), 60 parts of scaly graphite F#2 (manufactured by Nippon Graphite Industries Co., Ltd.) as the conductive carbon material (A-1), 10 parts of exfoliated graphite UP-20 (manufactured by Nippon Graphite Industries Co., Ltd.) as the conductive carbon material (A-2), 150 parts of the solution of binder resin (1) (resin solid content 30 parts), and 137 parts of toluene / isopropyl alcohol (mass ratio: Tol / IPA=1 / 1) as a solvent were mixed in a mixer, and further dispersed for 6 hours with a sand mill to obtain a conductive composition (1). Then, this conductive composition (1) was applied using a doctor blade onto a PET film having a thickness of 100 μm as a sheet-like substrate, and then heated and dried to produce a conductive film (1) having a thickness of 30 μm. The conductive film thus obtained was evaluated by the following methods. The evaluation results are shown in Table 1.

[0117] (Orientation degree of conductive film) The degree of orientation was evaluated by pole measurement, which is a parallel beam reflection method, using an X-ray diffraction device, Rigaku Smartlab. Specifically, a preliminary measurement (2θ scan) was performed, and the diffraction angle (2θ = 25°), which is the 002 reflection of graphite, was fixed using the obtained measurement profile, and the orientation distribution of the diffraction intensity was measured in the sample tilt angle direction from 0 to 90° in a step width of 1° with a step width of 1° and a scanning speed of 200° / min while rotating the sample 360° in the in-plane direction. Furthermore, background correction was performed, and the degree of orientation was calculated from the following formula. A =(180-Wi) / 180×100 A: Degree of orientation (%) Wi: Average in-plane full width at half maximum of the peak obtained as a result of intensity measurement

[0118] (Gloss of conductive film) The gloss of the conductive film was evaluated using micro-TRI-Gloss (manufactured by BYK Additives & Instruments). Specifically, the micro-TRI-Gloss was placed in contact with the conductive layer surface, the 60° gloss value was measured at three points, and the average value was calculated as the 60° gloss value.

[0119] (Conductive film density) The density of the conductive film was evaluated from the mass and volume of the conductive film. Specifically, a 10 cm square PET film (area: 100 cm) with a conductive film laminated thereon was 2 ) and the mass and thickness of a 10 cm square PET film (area: 100 cm 2 ) and measure the mass and thickness of the conductive film (area: 100 cm 2 The mass and thickness of the conductive film were then calculated. The mass of the conductive film was then divided by the volume (area x thickness) to calculate the density of the conductive film.

[0120] (Volume resistivity of conductive film) The volume resistivity of the conductive film was determined by measuring with a four-terminal method (JIS-K7194) using Loresta GP (manufactured by Mitsubishi Chemical Analytech Co., Ltd.). (Evaluation criteria) ◎◎: Volume resistivity is 3×10 -3 Less than Ω·cm (very good) ◎: Volume resistivity is 3×10 -3 Ω cm or more, 1×10 -2 Less than Ω cm (good) ○: Volume resistivity is 1×10 -2 Ω cm or more, 5×10 -2 Less than Ω cm (usable) △: Volume resistivity is 5×10 -2 Ω cm or more, 1×10 -1 Less than Ω·cm (poor) ×: Volume resistivity is 1×10 -1 Ω·cm or higher (very poor)

[0121] (Conductive film conductivity retention rate) The conductivity retention rate of the conductive film was determined from the rate of change in volume resistivity before and after leaving it in an oven at 80° C. for one month (percentage of the ratio of volume resistivity before leaving it in the oven / volume resistivity after leaving it in the oven for one month). The volume resistivity was measured in the same manner as above. (Evaluation Criteria) ◎: Change rate is 120% or less (good) ○: Change rate is greater than 120% and less than 200% (usable) △: Change rate is greater than 200% and less than 300% (poor) ×: Change rate is 300% or more (extremely poor)

[0122] (Durability of conductive film) The durability of the conductive films prepared above was evaluated by scratch hardness (pencil method) (based on JIS K5600-5-4:1999). The durability of each coating film was evaluated using a pencil with hardness of HB. (Evaluation criteria) ◎: No plastic deformation or cohesive failure occurs (good) ○: Some plastic deformation and cohesive failure have occurred (usable) △: Plastic deformation or cohesive failure occurred about halfway (bad) ×: Plastic deformation and cohesive failure occurred in most parts (very poor)

[0123] (Examples 2 to 22) Using the materials and composition ratios shown in Table 1, conductive films (2) to (22) were obtained in the same manner as for conductive film (1).

[0124] Example 23 Among the conductive carbon materials (A), 50 parts of the boron-containing carbon material (A-1-3) as the conductive carbon material (A-1), 10 parts of the boron-containing carbon material (A-2-1) as the conductive carbon material (A-2), 10 parts of the boron-containing carbon material (A-2-2) as the binder resin, 10 parts of the water-soluble resin PVP K-30 (polyvinylpyrrolidone, manufactured by ISP Japan Co., Ltd.) as the binder resin, and 237 parts of water were mixed in a mixer, and further dispersed in a sand mill to obtain a dispersion. 40 parts (20 parts of resin solids) of polyacrylic emulsion W-168 (50% solids by mass, manufactured by Toyochem Co., Ltd.), which is an aqueous resin fine particle, was further added to this dispersion as the binder resin, and dispersed in a sand mill to obtain a conductive composition (21). Then, this conductive composition (21) was applied onto a PET film having a thickness of 100 μm, which served as a sheet-like substrate, using a doctor blade, and then heated and dried to produce a conductive film (23) having a thickness of 30 μm.

[0125] Comparative Example 1 A conductive composition (24) was prepared in the same manner as the conductive composition (1), except that the dispersion time in the sand mill was changed to 30 minutes, using the materials and composition ratios shown in Table 1. Then, this conductive composition (24) was applied to a PET film having a thickness of 100 μm, which was to serve as a sheet-like substrate, using a doctor blade, and then heated and dried to prepare a conductive film (24) having a thickness of 30 μm.

[0126] Comparative Example 2 Conductive composition (25) was prepared by the same method as conductive composition (24) using the materials and composition ratios shown in Table 1. Then, this conductive composition (25) was applied to a PET film having a thickness of 100 μm, which was to be a sheet-like substrate, using a doctor blade, and then heated and dried to prepare a conductive film (25) having a thickness of 30 μm. Furthermore, the conductive film was hot-pressed at 50° C. to adjust the density of the conductive film to 1.9 g / cc and the gloss to 42.

[0127] [Table 1]

[0128] As shown in Table 1, the conductive film of the present invention has improved conductivity and durability more than ever before, and is able to achieve both. On the other hand, in Comparative Examples 1 and 2, poor conductivity and durability were observed. In Comparative Example 1, the carbon material aggregated and was distributed unevenly, so the degree of orientation of the conductive film was low, which led to a decrease in gloss and density, and it was confirmed that the conductivity and durability were deteriorated. In Comparative Example 2, the gloss and density were improved and the durability tended to improve, but the conductivity was still low. It is believed that the arrangement of the carbon particles, which have high conductive anisotropy, was irregular, inhibiting the conductive network between the particles and reducing the conductivity. From this, it can be seen that the degree of orientation is important for improving the conductivity. It was also confirmed that the conductivity decreased when stored for a long period of time. This is thought to be because the contact points between the carbon materials were formed by external pressure from the press, and the contact points separated when stored for a long period of time, making it impossible to maintain conductivity. In contrast, in Examples 1 to 23, which had a high degree of orientation, a conductive film was obtained that could achieve both conductivity and durability better than before. In particular, it can be seen that Examples 9 to 13, which combined three types of carbon materials, had good conductivity. It is expected that the combination of carbon materials with different particle sizes improved the degree of orientation and improved the conductive network between the particles, leading to the improvement. In addition, in Examples 14 to 23, which included a boron-containing carbon material, the conductivity and durability of the coating film were further improved. This is thought to be because, in addition to the effect of improving conductivity by doping with boron, the conductive network between the carbon materials was strengthened by improving the adsorption rate of the resin. As described above, it was found that in a conductive film containing a binder resin and a conductive carbon material, by controlling the orientation of the conductive film, it is possible to form an excellent conductive network between the carbon materials, thereby exhibiting excellent conductivity and durability.

Claims

1. A conductive film comprising a conductive carbon material (A) and a binder resin (B), wherein the conductive carbon material (A) comprises two or more types of carbon materials having different average particle sizes, and the degree of orientation in the carbon (002) plane measured by X-ray diffraction (XRD) is 70% or more.

2. 2. The conductive film according to claim 1, wherein the 60° gloss is 4 to 30.

3. 3. The conductive film according to claim 1, having a density of 1.2 to 2.0 g / cc.

4. 4. The conductive film according to claim 1, wherein the conductive carbon material (A) contains a boron-containing carbon material.

5. 5. The conductive film according to claim 4, wherein the boron content of the boron-containing carbon material is 0.005 to 15 mol %.

6. A conductive device comprising the conductive film according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Graphite powder and lubricant and black ink using the same

    JP1990204317A

  • Conductive resin composition and molding using the same

    JP2001060413A

  • Method for preparing electroconductive resin composition and fuel cell separator using the electroconductive resin composition

    JP2011195618A

  • Resin composite material and method for producing the same

    JP2013119577A

  • Conductive wiring sheet

    JP2019005993A